Dungeons & Dragons : honor among thieves, The feast of the moon - Lambert, Jeremy, 1989- (IDW Publishing, 2023)
When their latest heist ends in failure, Edgin and his band of thieves find themselves stranded in a town under siege! The Bandit King and his thugs have been extorting the locals for years, but nothing is what it seems, and, as the Feast of the Moon begins, a greater evil lurks. Edgin and his friends--roguish Forge, barbarian Holga, and sorcerer Simon--promise to help, but will they honor their word? Or will the unlikely heroes abandon the last of the Harper principles Edgin used to hold so dear? Then, in a special bonus story, the paladin known as Xenk swore to protect an artifact of dangerous and mysterious power. But the terrors of the Underdark will test his oath more than he could have imagined!